Effect of caffeine on maximal oxygen uptake in wheelchair rugby players: A randomized, placebo-controlled, double-blind study - Iva Klimešová; Iva Machová; Aleš Jakubec; John Corkle (Palacký University Olomouc, 2017)
Background: The positive effects of caffeine supplementation on strength-power and endurance performance in healthy athletes have been demonstrated in many studies. A possible mechanism for its ergogenic effect relates to its influence on the central nervous system. Post-traumatic complications in cervical spinal cord injury affect almost all body systems including the nervous system. For this reason, we expect that caffeine will have a different effect of performance in the group of athletes with spinal cord injuries. Objective: To examine the effects of caffeine supplementation on maximal aerobic power in elite wheelchair rugby players. Methods: Seven elite male wheelchair rugby players with complete cervical-level SCI (C4-Th1) were recruited (mean age: 28 ± 5.42 years; mean body mass index: 26 ± 2.84 kg/m2). The effect of caffeine was assessed by an incremental arm ergometer test until volitional exhaustion. The maximal oxygen uptake (VO2max/kg), maximum power (W max/kg), peak heart rate (HR peak), and intensity of perceived exertion (RPE) were measured. Participants performed the test twice with a two-week washout period. One hour before each exercise test subjects ingested a capsule of placebo or caffeine (3 mg per kg of body weight). The tests were applied in a double-blind, randomized, repeated-measures, and cross-over design. Wheelchair rugby players were chosen because of the expected high homogeneity of participants - in terms of the type and degree of disability, gender, and age of the players. Results: The monitored parameters were not significantly influenced by caffeine intervention as compared to placebo: VO2max/kg (p = .40), W max/kg (p = .34), HR peak (p = .50) and RPE (p = .50). Conclusions: The current findings suggest that a caffeine dose of 3 mg/kg body mass does not improve oxygen uptake and maximal power in elite wheelchair rugby players.